Characterization of volatile metabolites associated with confinement odour during the shelf-life of vacuum packed lamb meat under different storage conditions. (March 2016) - Reis, Marlon M.; Reis, Mariza G.; Mills, John; Ross, Colleen; Brightwell, Gale
Abstract: Confinement odour was investigated. Volatiles were extracted directly from the pack, using solid phase microextraction and analysed by gas chromatography–mass spectrometry. Sensory evaluation and microbiological analysis of the meat surface were also performed. Commercial samples of vacuum packed lamb legs (n = 85), from two meat processing plants, were kept for 7 weeks at − 1.5 °C then at different regimes of temperature (− 1.5 to + 4 °C) until 11, 12 or 13 weeks. Persistent odour was observed in 66% of samples, confinement odour in 24% and no odour in 11%. Volatiles associated with confinement odour (3-methyl-butanal, 3-hydroxy-2-butanone and sulphur dioxide) corresponded with end/sub products of glucose fermentation and catabolism of amino acids by bacteria (all bacteria naturally found in meat and do not represent a risk to health). Confinement odour could indicate a stage at which the environment for bacteria growth is becoming favourable for the production of volatiles with strong odours that are noticed by the consumer. Highlights: Evaluation of volatiles in chilled lamb vacuum packed produced during storage up to 13 weeks Effect of length and temperature of storage on production of volatiles in chilled lamb vacuum packed Volatiles associated to confinement odour investigated and connected to bacterial growth